Reasons for Teacher Turnover : A study conducted on school teachers in Dubai - Ahuja, Sumita (2010)
The project is an aim to investigate the reasons due to which teachers leave their jobs in Dubai. Dubai, by character is a country where about eighty percent of the population is expatriate population. Two different systems of education run parallel to serve the population of Dubai. The public school system caters to the local population and the private school system which serves mainly the children of the expatriates in the country. The public schools are run and managed by locals with a few native speakers and the private schools are run and managed by the expatriates of different countries. Whereas there are a variety of public schools, the variations are not as many as in the private schools. There are schools of varying countries, curriculums, and fee structures so much so that doing a study of this kind is very difficult without making generalizations which sometimes may not be very accurate. However from our experiences as a teacher and a student of education, we had a hunch that Teacher turnover is as big, if not a bigger problem in Dubai as it is in other countries of the world. Though we could not estimate the actual volume of turnover as schools and school groups were very hesitant in giving any sort of information, we could get enough data to study the reasons for teacher turnover in Dubai and on the basis of that make some policy suggestions to reduce turnover in Dubai. The methodology followed was that of questionnaires and interviews. It was revealed that “dissatisfaction” with their jobs is one of the biggest reasons of teacher turnover in Dubai. When investigated further, many reasons of teacher dissatisfaction came to the fore and “salaries and benefits” headed the list of reasons for teacher dissatisfaction. Based on our results, we have outlined policy measures which can prove useful in reducing turnover of teachers. It has been a long journey of many months of hard work in groundwork, data collection and final analysis but we are satisfied that we have been able to undertake a unique study, studying turnover in Dubai from various angles and finding solutions to overcome it.